2014
DOI: 10.3390/ma7042913
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Applications for High K Materials in VLSI Technology

Abstract: The current status of High K dielectrics in Very Large Scale Integrated circuit (VLSI) manufacturing for leading edge Dynamic Random Access Memory (DRAM) and Complementary Metal Oxide Semiconductor (CMOS) applications is summarized along with the deposition methods and general equipment types employed. Emerging applications for High K dielectrics in future CMOS are described as well for implementations in 10 nm and beyond nodes. Additional emerging applications for High K dielectrics include Resistive RAM memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 161 publications
0
83
0
1
Order By: Relevance
“…125,126 We do note that the above mentioned film thicknesses are significantly higher than those typically utilized in traditional Si CMOS high-k dielectric applications where thicknesses of <10 nm are more common. [2][3][4][5][6][7][8] However, many of the applications involving these materials as diffusion barriers, 27,31,127 nano-resonators, 80,81 and piezoelectric transducers 43,87 can require significantly higher thicknesses of 20-1000 nm. Also, use of film thicknesses >100 nm minimize substrate 128 and interfacial thermal boundary resistance 129 effects that can complicate the mechanical and thermal property measurements, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…125,126 We do note that the above mentioned film thicknesses are significantly higher than those typically utilized in traditional Si CMOS high-k dielectric applications where thicknesses of <10 nm are more common. [2][3][4][5][6][7][8] However, many of the applications involving these materials as diffusion barriers, 27,31,127 nano-resonators, 80,81 and piezoelectric transducers 43,87 can require significantly higher thicknesses of 20-1000 nm. Also, use of film thicknesses >100 nm minimize substrate 128 and interfacial thermal boundary resistance 129 effects that can complicate the mechanical and thermal property measurements, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…44,45 For such devices, knowledge of properties such as Young's modulus and film stress are critical for predicting the flexure and resonance frequencies of bridged and cantilevered switches and sensors, [46][47][48][49] stretched transistor device performance, 50,51 buckling failures in nanopatterned structures, 52,53 and macroscale buckling and nanoscale wrinkling effects for stiff high-k films deposited on compliant polymeric substrates. 54,55 Unfortunately, only a limited number of studies have reported on the thermal [56][57][58][59] and mechanical 42,[60][61][62][63][64][65][66] properties of ALD highk dielectric materials, and the numerous reviews [2][3][4][5][6][7][8] of high-k dielectrics have focused primarily on the electronic structure and interfacial properties of high-k dielectrics from a CMOS device perspective. To the authors' knowledge, a clear correspondence between thermal/mechanical and electrical/optical properties for ALD high-k dielectrics has yet to be established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 For superior device performance at sub 10 nm nodes, germanium is being considered as an alternate channel material, owing to its intrinsic high mobility (electrons: 3900 cm 2 V À1 s…”
Section: Introductionmentioning
confidence: 99%
“…Hafnium (Hf)-based compounds such as HfO 2 , Hf-silicate, and nitride Hf-silicate have been intensively studied as candidate materials to replace SiO 2 in advanced metal-insulator-semiconductor field-effect transistors (MISFETs). [1][2][3][4][5][6][7] Hf-silicate is a most promising material because of its relatively high dielectric constant when compared with that of SiO 2 (ε r = 10−20, depending on Hf content 8 ), wide band gap (E g ∼6 eV), large (1.5 eV) conduction band offset to Si, 9 and low interface state density with Si (D it = 1-6×10 11 cm 2 eV 1 ). 4 Another highly attractive feature of Hf-silicate is its thermodynamic stability when directly deposited on Si substrates.…”
mentioning
confidence: 99%